2020
DOI: 10.3390/diseases8030032
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Infectious Complications in Children with Hematologic Malignancies and Chemotherapy-Induced Neutropenia

Abstract: Infections frequently complicate the treatment course in children with hematologic malignancies undergoing chemotherapy. Febrile neutropenia (FN) remains a major cause of hospital admissions in this population, and respiratory tract is often proven to be the site of infection even without respiratory signs and symptoms. Clinical presentation may be subtle due to impaired inflammatory response. Common respiratory viruses and bacteria are widely identified in these patients, while fungi and, less commonly, bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Immunocompromised children are at risk of pneumonia due to opportunistic pathogens, especially prolonged corticosteroid therapy was found to be a risk factor in pneumocystis pneumonia in pediatric patients 38 . Chemotherapy, which causes bone marrow insufficiency, is also a principal factor in causing pneumonia in pediatric patients 39 . In our study, intensive systemic treatment was not found to be statistically related to pneumonia in pediatric patients, but all pediatric patients diagnosed with pneumonia had received systemic treatment for more than 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocompromised children are at risk of pneumonia due to opportunistic pathogens, especially prolonged corticosteroid therapy was found to be a risk factor in pneumocystis pneumonia in pediatric patients 38 . Chemotherapy, which causes bone marrow insufficiency, is also a principal factor in causing pneumonia in pediatric patients 39 . In our study, intensive systemic treatment was not found to be statistically related to pneumonia in pediatric patients, but all pediatric patients diagnosed with pneumonia had received systemic treatment for more than 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary CT examination is strongly recommended. In this study, the imaging of children with pneumonia were mainly characterized by ground glass shadow, consolidation shadow, streak shadow and nodule shadow, which suggested bacterial and/or fungal infection(Nambu et al 2014;Voulgaridou et al 2020).…”
mentioning
confidence: 83%
“…ere are no specific case reports or clinical investigations analyzing M. pneumoniae infections in children affected with congenital neutropenia [24,48,49]. Notably, there is no evidence that acquired neutropenia in children with cancer significantly predisposes to M. pneumoniae pneumonia; conversely, recent studies showed a correlation between neutrophil number and extravasation into the lungs with the severity of M. pneumoniae pneumonia in this clinical setting [50,51].…”
Section: Innate Immunity Defectsmentioning
confidence: 99%
“…There are no specific case reports or clinical investigations analyzing M . pneumoniae infections in children affected with congenital neutropenia [ 24 , 48 , 49 ]. Notably, there is no evidence that acquired neutropenia in children with cancer significantly predisposes to M .…”
Section: Innate Immunity Defectsmentioning
confidence: 99%